EFFICIENCY OF PEGYLATED INTERFERON ALPHA AS MONOTHERAPY IN CHRONIC HEPATITIS DELTA INFECTION - Bahcecioglu, I. H.; Aygun, C.; Gozel, N.; Bulut, Y. (Elsevier Science Bv, 2010)
[Abstract Not Available]
45th Annual Meeting of the European-Association-for-the-Study-of-the-Liver -- APR 14-18, 2010 -- Vienna, AUSTRIA